(3cJGH BOGH GdadGSaIs - (3eMeO Hf CMeO Hf Ydj Hf EHQGgje Hf CMeO Hf eMeO GdCfUGQjs
(3ChdgG (B:s
(3gPg fhGOQ CdaGX GdadGSaI GdMceGA hBOGH GdeYdejf GdbOeGA GdPjf CUdhG GdMceI haQhYgG hCPGYhgG ai YGdege , hTQYhgG MJi YQa Hge hfbdJ Yfge hge CSGWjagG hOYGFegG s
(3BNQgG (B:s
(3adeG aQZhG ef cdGege CKHJ SdjeGf Udi Gddg Ydjg hSde LejY Pdc ai MceJg hYGO Edi ehVYI Je GdcJGH HMeO Gddg hMSf Yhfg s
(3GdfSNI HgG MhGTs
(3fSNI fajSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs